Bahasa Inggris - Aulia Zahra, Aulia Zahra Aulia (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2023)
This study aims to analyze the typology of Chinese ethnicity based on aspects of religious life and Chinese ethnic organization in Minangkabau. In West Sumatra, the presence of ethnic Chinese can be found in the Kampung Pondok sub-district, South Padang District, Padang City. For the people of Padang City and its surroundings, this residential area is often called Kampung Cino. The most prominent evidence to date is the See Heen Kiong Temple. So far there is not much literature that discusses the typology of Chinese ethnicity in the city of Padang, so an effort is needed to complement the existing literature. This study used a case study qualitative research method, the Chinese ethnic group studied in Padang City. Data obtained by means of documentation. This study found that there are two typologies of ethnic Chinese in Minangkabau. First, based on religion, Chinese Muslims in the ethnic Chinese Muslim community in Padang city are members of the Indonesian Chinese Islamic Association (PITI). Second, based on ethnic similarities.